Determinant Factors of Revisit Intention to Museum: Integration of Technology Acceptance Model and Expectation Confirmation Theory - Intan Istiqomah (Journal of Computer Science and Informatics Engineering, 2025)
The development of digital technology is progressing very rapidly. Museums as cultural centers need to adopt digital technology to give different experiences for visitors. Museum Sonobudoyo also starts using digital technology. The technology used varies, from animated films, Virtual Reality (VR), to interactive screens. Visitors can enjoy these technologies and may revisit the museum if they are satisfied. This research tries to examine the factors that determine revisit intention of the visitors from the perspective of Technology Acceptance Model and Expectation Confirmation Theory. Data collection was carried out during period May – June 2024 by distributing questionnaires to museum visitors. A total of 160 valid questionnaires were collected and processed using Partial Least Square Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3.0 software. The results show that the factors which determine revisit intention are perceived usefulness, using digital technology, confirmation, and satisfaction. This research contributes to the existing knowledge in museum’s technology adoption and integration between TAM and ECT theories. Not only theoretical contribution, the result of this research also has practical contributions to the development of museum strategies. By knowing the factors that may influence visitors’ revisit intention, museums may consider these factors when planning to use other digital technologies.